Remembering differently: Use of memory strategies among net-generation ESL learners. - Shakarami, Alireza; Abdullah, Mardziah Hayati; Abdullah, Mohd Faiz; Tan, Bee Hoon (Academic Journals, 2011)
Net-generation learners are growing up in an era when much of the learning, communication, socializing and ways of working take place through digital means. Living in this digital era may result in different ways of thinking, ways of approaching learning, strategies, and priorities. The Net-Geners therefore, need new skills and new strategies to perform successfully as learners and workers. This study used a mixed-methods approach to identify whether one such strategy, that is, memorization strategy may have changed for the Net-Generation language learners. The researchers, first obtained quantitative data from 107 ESL tertiary language learners about their strategy use based on Oxford's (1989) widely used Strategy Inventory for Language Learning (SILL), currently considered the most comprehensive inventory. Data on strategy use was then procured using qualitative methods such as semi-structured interviews, Open-ended questionnaires, and texts of the respondents' online interaction in a language task. This latter set of data was analysed (i) to compare the qualitative data with the SILL data, and (ii) to identify possible emergent memory strategies among Net-Geners. The study found that memory strategies have not faded from repertoire of strategies for Net-Genres language learners, rather a set of modifications have emerged in terms of storage place, methods of storing information, retrieval system, and use of memory strategies for successful language learning.